Trackins (Trk-Targeting Drugs): A Novel Therapy for Different Diseases - George N. Chaldakov; Luigi Aloe; Stanislav G. Yanev; Marco Fiore; Anton B. Tonchev; Manlio Vinciguerra; Nikolai T. Evtimov; Peter Ghenev; Krikor Dikranian (MDPI AG, 2024)
Many routes may lead to the transition from a healthy to a diseased phenotype. However, there are not so many routes to travel in the opposite direction; that is, therapy for different diseases. The following pressing question thus remains: what are the pathogenic routes and how can be they counteracted for therapeutic purposes? Human cells contain >500 protein kinases and nearly 200 protein phosphatases, acting on thousands of proteins, including cell growth factors. We herein discuss neurotrophins with pathogenic or metabotrophic abilities, particularly brain-derived neurotrophic factor (BDNF), nerve growth factor (NGF), pro-NGF, neurotrophin-3 (NT-3), and their receptor Trk (tyrosine receptor kinase; pronounced "track"). Indeed, we introduced the word trackins, standing for Trk-targeting drugs, that play an agonistic or antagonistic role in the function of TrkBBDNF, TrkCNT−3, TrkANGF, and TrkApro-NGF receptors. Based on our own published results, supported by those of other authors, we aim to update and enlarge our trackins concept, focusing on (1) agonistic trackins as possible drugs for (1a) neurotrophin-deficiency cardiometabolic disorders (hypertension, atherosclerosis, type 2 diabetes mellitus, metabolic syndrome, obesity, diabetic erectile dysfunction and atrial fibrillation) and (1b) neurodegenerative diseases (Alzheimer's disease, Parkinson's disease, and multiple sclerosis), and (2) antagonistic trackins, particularly TrkANGF inhibitors for prostate and breast cancer, pain, and arrhythmogenic right-ventricular dysplasia. Altogether, the druggability of TrkANGF, TrkApro-NGF, TrkBBDNF, and TrkCNT−3 receptors via trackins requires a further translational pursuit. This could provide rewards for our patients.